Metformin Reduces NGF-Induced Tumour Promoter Effects in Epithelial Ovarian Cancer Cells - Maritza P. Garrido; Renato Salvatierra; Manuel Valenzuela-Valderrama; Christopher Vallejos; Nicole Bruneau; Andrea Hernández; Margarita Vega; Alberto Selman; Andrew F. G. Quest; Carmen Romero (Pharmaceuticals, 2020)
Epithelial ovarian cancer (EOC) is a lethal gynaecological neoplasm characterized by rapid growth and angiogenesis. Nerve growth factor (NGF) and its high affinity receptor tropomyosin receptor kinase A (TRKA) contribute to EOC progression by increasing the expression of c-MYC, survivin and vascular endothelial growth factor (VEGF) along with a decrease in microRNAs (miR) 23b and 145. We previously reported that metformin prevents NGF-induced proliferation and angiogenic potential of EOC cells. In this study, we sought to obtain a better understanding of the mechanism(s) by which metformin blocks these NGF-induced effects in EOC cells. Human ovarian surface epithelial (HOSE) and EOC (A2780/SKOV3) cells were stimulated with NGF and/or metformin to assess the expression of c-MYC, β-catenin, survivin and VEGF and the abundance of the tumor suppressor miRs 23b and 145. Metformin decreased the NGF-induced transcriptional activity of MYC and β-catenin/T-cell factor/lymphoid enhancer-binding factor (TCF-Lef), as well as the expression of c-MYC, survivin and VEGF in EOC cells, while it increased miR-23b and miR-145 levels. The preliminary analysis of ovarian biopsies from women users or non-users of metformin was consistent with these in vitro results. Our observations shed light on the mechanisms by which metformin may suppress tumour growth in EOC and suggest that metformin should be considered as a possible complementary therapy in EOC treatment.